IMPLEMENTASI PIJAT OKSITOSIN DAN IMPLEMENTASI PIJAT OKSITOSIN DAN FIELD MASSAGE SEBAGAI TERAPI KOMPLEMENTER DALAM CONTINUITY OF CARE - Krismiyati, Murti; Fauziandari, Erma Nur; Putri, Rizka Mauliya (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2024)
Maternal and infant mortality is the most important measure in assessing indicators of the success of health services in Indonesia, but in reality there are also deliveries that experience complications resulting in maternal and infant mortality. According to the 2017 Indonesian Demographic and Health Survey (IDHS) the infant mortality rate (IMR) is 24 per 1,000 live births with 151,200 cases caused by low birth weight babies (LBW) and asphyxia. Based on DIY's health profile in 2021, there were 270 IMR in Yogyakarta City. Meanwhile, based on the health profile of Sleman in 2020, the number of infant deaths was 55 cases. Based on this, continuous midwifery care or Continuity Of Care needs to be implemented as an effort to reduce IMR. Continuing care delivery can use several complementary techniques. The technique used in midwifery care is oxytocin massage to stimulate milk production, and field massage has many benefits including preventing hyperbilirubinemia and increasing body weight. This type of research is a qualitative research method in the form of a Continuity of Care case study covering services for mothers and children from pregnancy to family planning. After oxytocin massage, there was an increase in milk production in postpartum mothers as evidenced by the 6th day the milk that came out was smooth, and field massage was proven to increase weight in infants as evidenced by an increase in baby weight of 100 grams in 6 days and no signs of hyperbilirubin or jaundice.